Evaluation of grace-based combined geopotential model over the Baltic countries - Ellmann, Artu; Jürgenson, Harli (Geodesy and Cartography, 2012)
Nowadays, many geodetic and engineering applications require that the two essential components of the vertical positioning – the height and the corresponding reference surface (geoid), are determined precisely. The recent advancements of satellite technology have resolved the long-wavelength component of the global geoid with an accuracy of a few cm. The tracking data of the GRACE twin-satellites are the basis for the new combined geopotential model EIGEN-GL04c. Th is contribution assesses the quality of this model through comparisons with an earlier geopotential model (EGM96) of the Baltic countries. The method of spherical harmonic expansions is used in numerical investigations. The results of evaluation revealed signifi cant discrepancies between the long wavelength contributions of the models, which may reach several decimetres in terms of the geoidal heights. Th ere are also some notable improvements of numerical statistics (assessed by the GPS-levelling data) in the target area, when utilizing the new EIGEN-GL04c, instead of using the EGM96. A decimetre level accuracy can be obtained for the EIGEN-GL04c derived geoid model, provided that any datum inconsistencies have been eliminated. Th is creates necessary preconditions to further improve the geoid models on the regional scale. Kombinuotojo grace duomenimis pagrįsto geopotencialinio modelio vertinimas Baltijos valstybių teritorijose Daugumai geodezijos ir inžinerijos sričių vertikaliajai padėčiai nustatyti būtina, kad du komponentai – aukštis ir atitinkamas atramos paviršius (geoidas) – būtų tiksliai apibrėžti. Nūdienos palydovinės technologijos laimėjimai leidžia globalinio geoido ilgųjų bangų komponentę nustatyti kelių centimetrų tikslumu. Pagrindas naujam kombinuotajam geopotencialiniam modeliui EIGEN-GL04c sudaryti yra GRACE palydovų-dvynių stebėjimų duomenys. Straipsnyje analizuojama šio modelio kokybė, palyginti su ankstesniu geopotencialiniu modeliu (EGM96 – Earth Geopotential Model 1996), Baltijos valstybių teritorijose. Skaitinei analizei taikomas sferinių harmonikų metodas. Ištyrus paaiškėjo žymūs modelių skirtumai. Išreiškiant geoido aukščiais, jie siekia keletą decimetrų. Be to, tiriamoje teritorijoje taikant naująjį EIGEN-GL04c modelį vietoje EGM96 pastebėta tam tikras statistinis pagerėjimas (gaunamas pagal GPS ir niveliavimo duomenis). Taikant EIGEN-GL04c modelį pasiekiamas decimetrinis geoido aukščių nustatymo tikslumas. Tai sudaro reikalingas prielaidas regioniniams geoido modeliams tobulinti. First published online: 03 Aug 2012